Examining the relationship between physical activity and academic performance among primary students at Tumu in the Upper West Region of Ghana - Dimbie, Mohammed; Akude, Seyram Kafui; Dapilee, Felicia (Research Journal in Advanced Social Sciences, 2022)
Much research has shown a link between physical activity and students' academic success in school. In recent years, this approach has gained significant traction, particularly in the context of the professional education system. To investigate the association between physical activity and academic achievement in pupils studying in elementary schools, the research team set out to conduct a survey. The purpose of this study is to discover the connections between the two the study's primary objectives was to investigate the association between physical exercise and academic achievement. According to the findings, the study was a cross-sectional study in which 40 students took part. Prior to beginning the investigation, an ethical clearance was obtained. The instruments utilised to acquire data from students were interviews and observation, and the responses supplied by them were then assessed by the researchers. The findings of the study revealed that most students agreed that there was a link between physical exercise and academic achievement, since their test scores were higher than those of students who did not participate in physical activities during their free time. The findings suggest that physical activities can help students focus better on their studies and may even help them achieve academic success.